Mitigating First Year Burnout: How Reimagined Partnerships Could Support Urban Middle Level Teachers - Stephanie Behm Cross; Clarice Thomas (Middle Grades Review, 2017)
Given what we know about new teacher attrition—most teachers leave within their first five years in the field—specialized support during early years of teaching is critical. But should this support look different across different contexts and grade bands? What does supportive teacher education and induction look like for middle level educators preparing to teach in urban settings? This essay describes steps taken to design a cross-institutional, collaborative 3-year residency program for K-8 educators, and speaks to the importance of reimagined co-teaching, critical, and cross-institutional partnerships in middle grades teacher education. The authors urge readers to consider how to implement similar modifications in their own spaces to create powerful, collaborative middle grades teacher education and induction.
Keywords: co-teaching; collaboration; cross-institutional partnerships; residency; race